Local District Science Programs: Present Status and Future Trends with Implications for Teacher Training. - Tamppari, Raymond; Johnson, Gordon (Science Education)
The article discusses the present status of science program innovations and future trends in science enrollment significant in teacher training in Arizona. An important trend in the science programs of secondary schools to the science teacher is the changes in enrollments in science classes, which determine the level to which positions will be available. The result of the study provided basis for the determination of some of the capabilities demanding new teachers in the state. The capabilities give some guidance to the prospective science teachers and the persons responsible for their pre-service experiences.